The impact of corporate governance and organizational ambidexterity in performance: Evidence from European banks - Pereira, Gonçalo Filipe Mendes (2021)
The banking sector in Europe has met several changes during the latest decade, which brought to light new subjects into the field of banking management. On one hand, the change in regulations caused corporate governance to become a recurring topic to address agency problems arising from misaligned objectives. On the other hand, progress and innovation made banks rethink their strategies, with organizational ambidexterity gaining popularity as a strategic approach to gain competitive advantage in a dynamic environment. In this study, we sought to investigate the role of the two subjects mentioned above in achieving a superior financial performance. Our results demonstrate that whilst there seems to be a positive effect of relative exploration on ROA, the conclusions regarding the corporate governance mechanisms are mixed: we did not find a significant influence of the ESG score on performance, but we did find that board characteristics have an effect on ROA. Additionally, our research contributes to the rather unexplored theme on whether there is a connection between organizational ambidexterity and corporate governance, which did not yield statistically significant results.